Effect of exogenous fibrolytic enzyme supplementation on rumen fermentation in sacco NDF disappearance and total tract nutrient digestibility of feedlot steers fed hominy chop - maize based diets - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2020)
Dissertation (MSc (Agric))--University of Pretoria, 2020.